A Customized Production Performance Model Based on Preparation, Discipline, Compactness, and Cleanliness in a Bentonite Plant - Agustinus Hariadi Djoko Purwanto; Mohammad Fazli Sabri; Sri Hartono (Politeknik Siber Cerdika Internasional, 2026)
Background: A bentonite plant producing high-performance bleaching earth faces challenges in competition due to its decreasing level of production effectiveness and efficiency including increasing reports of non-conforming products, defected products and reduced production volume. Realizing the factory have applying 5S to prevent and handle such problems, a customized model extracted from the 5S is proposed. Objective: This research examines the proposed operation management model for which the production is capable to conform with planned quality and quantity as well as preventing rejects. Methods: The model is structured from Preparation simultaneously affects Discipline, Compactness and Cleanliness. Subsequently, the three-process management improves implementation consistency from which production effectiveness is attained. This is a quantitative study in which data collected from 140 respondents and analyzed using PLS software. Results: The results reveals that Preparation affects Discipline, Compactness, and Cleanliness at values of 0.685, 0.695, and 0.621 respectively. Discipline increases Implementation consistently at a value of 0.329, Compactness at 0.267 and Cleanliness at 0.233. Finally, the implementation consistency increases production performance at 0.717. In summary, the customized model is fit to be implemented for recovering the plant’s production performance. Conclusion: The proposed customized model derived from the 5S framework is validated and demonstrates strong applicability for recovering production performance in a bentonite plant. Theoretically, this study contributes a structured cause-effect model linking preparation, discipline, compactness, and cleanliness to implementation consistency and production effectiveness. Practically, plant managers are provided a field-tested, quantitatively validated framework for systematic improvement of production operations.